FORMULATION AND EVALUATION OF MEDICATED CHEWING GUM OF TERBUTALINE SULFATE FOR THE ASTHAMATIC MANAGEMENT - MISHRA, SHWETA; SHAH, SUNIL KUMAR; BK, DUBEY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This experiment aimed to improve the bioavailability of terbutaline sulfate by formulating it as medicated chewing gum. Methods: By employing zein as the gum foundation and the melting process, chewing gum was created with the desired outcome. Results: All formulations had thicknesses ranging from 3.61 to 3.68 mm in the lateral direction and from 5.22 to 5.41 mm in the longitudinal direction. All formulations had hardness values between 3.1 and 3.4 kg/cm2. All formulations had weight variations between 1.6% and 2.1%. All of the formulations had the same quantity of medication, which varied between 95.2 and 96.9%. Drug release from terbutaline sulfate chewing gum (TCGs) in simulated saliva (pH 6.8 buffer solution) was investigated by examining the samples up to a half-hour later. It was discovered that the drug release from the formulations ranged from 64.28 to 89.56% in 30 min. Conclusion: The release of the medication was reduced when the gum basis (zein) content in the formulations was increased. It was discovered that, after 30 min, TCG1 emitted the most proportion of terbutaline sulfate. As a result, it may be regarded as the finest formulation available.